Enhancing Surveillance : Interconnectedness and Clusters. (Policy Papers; Policy Paper ;, 2012)
This paper and the companionabackground paperpresent a simple conceptual framework to better understand cross-border trade and financial interconnectedness. Countries are grouped together into 'clusters' on the basis of having relatively tight trade and financial connections (e.g., Asian supply chain). Clusters are connected to one another through 'gatekeepers' (e.g., Austria is a gatekeeper to the Central and Eastern Europe, and Sweden to the Baltics), and countries that are central to the whole network are in the 'core' (the systemic-5). By mapping this architecture of cross-border trade and financial interconnectedness, the papers provide-at a glance-an easy way to comprehend the direct and indirect linkages of countries. The papers suggest that gatekeepers in particular can play a role in dampening or amplifying and propagating shocks, and this role depends on the economic context and policy space.